Treatment outcomes, antibiotic selection, and related factors in the management of diabetic foot infections in Vietnam - Tan To Anh Le; Viet An Tran; Minh Hoang Phan; Minh Chau Tran; Hoang Toan Ngo (Endocrine and Metabolic Science, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) stands as the foremost risk factor for infected foot ulcers, contributing to a myriad of chronic complications including cardiovascular, renal, neuropathic, vascular, and podiatric issues. Employing suitable antibiotic therapy becomes imperative in managing Diabetic Foot Infections (DFIs). This study endeavors to assess the efficacy of antibiotic treatment in addressing infected foot ulcers among patients with T2DM in Vietnam. Methods: A descriptive cross-sectional study with analysis was performed on 830 T2DM patients (67 patients with DFIs were treated with antibiotic therapy to evaluate treatment outcomes). Results: Among T2DM patients, 8.07 % had infected foot ulcers, with an average age of 62.5 ± 11 years and a female-to-male ratio of 2.9:1. Ulcer healing post-antibiotic treatment was 88.06 %, with 35.82 % aligning initial antibiotic treatment with antibiogram results. Bacterial resistance rates were high for Cephalosporin (>60 %), Ampicillin/Sulbactam (91.67 %), and Quinolone groups (>60 %), while Carbapenem group showed high sensitivity (>73 %). Initial empiric antibiotic treatment response was associated with osteomyelitis existence and ulcer healing outcomes (p < 0.005). Wagner grade > 2, elevated CRP levels, and atherosclerotic stenosis were associated with lengthy clinic stays. Conclusion: Selecting the proper antibiotic regimen is crucial in effectively managing Type 2 Diabetic Foot Infections. Identifying the risk factors associated with treatment outcomes is imperative to mitigate adverse effects on foot infection treatment outcomes among T2DM patients in Vietnam.